Nexus Ecotheology Curriculum Standards Policy: A Strategic Solution to Overcome Epistemological Fragmentation of Education at IAIN Pontianak - Noviansyah (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
West Kalimantan, as the epicenter of the world's lungs, continues to face the threat of massive environmental degradation, yet Islamic education at IAIN Pontianak remains trapped in a textual-sky paradigm that is sterile from ecological issues. The focus of this study is to formulate a curriculum reorientation through the Ecotheological Nexus standards to address epistemological fragmentation. The main gap is found in the sharp separation between theological doctrine and natural responsibility, where the curriculum exists dichotomously and anthropocentrically. Specific issues examined include the dominance of sectoral egos of scientific disciplines and the absence of integrative instruments in the curriculum, courses, and Semester Learning Plans (RPS). This study is urgent to maintain the institution's relevance amidst the global climate crisis. Using a descriptive qualitative approach with a case study design, this policy study makes IAIN Pontianak's curriculum documents the primary object of study through document analysis instruments. The results show that scientific fragmentation causes students to experience